Consumer behaviour in mobile social media: A study of Chinese cosmetic buyers in WeChat - Zhiqing Wen (2020)
The growth of Chinese Cosmetic Market and use of WeChat to make various purchases especially cosmetics by the users have garnered significant attention. However, there is a lack of empirical studies examining consumer behaviour when it comes to purchasing cosmetics on WeChat by the WeChat users. This study attempts to fill that gap in the literature. First, by surveying the existing literature, this study constructs a modified version of Decomposed Theory of Planned Behaviour. Second, using survey, data are collected from 150 Chinese WeChat users. And finally, Regression Analyses are used for validating the proposed model. The findings of this study indicate that Attitude and Perceived Behaviour Control have significant influence on WeChat users’ Behaviour Intention, but such influence was not observed for Subjective Norms and Bandwagon Effect. The findings of this study will help cosmetic companies to formulate effective promotion strategies to enhance consumers’ Behaviour Intention to purchase their products on WeChat. Furthermore, companies must ensure the ease of use and compatibility of their systems to influence higher purchase intention for their users.